Catalytic C3 aza-alkylation of indoles. Issue 32 (28th July 2020) - Bonandi, Elisa; Perdicchia, Dario; Colombo, Eleonora; Foschi, Francesca; Marzullo, Paola; Passarella, Daniele
Abstract : The aza-alkylation reaction at position 3 of the indole scaffold allows the introduction of a differently substituted aminomethyl group, with the formation of a stereogenic centre. Critical summary of 2000–2019 meaningful papers. Abstract : The aza-alkylation reaction at indole's C3 position allows the introduction of a differently substituted aminomethyl group, with the formation of a new stereogenic centre. The reaction involves essentially three different partners: an indole, aldehyde and amine. The formation of the reactive iminium species can be catalyzed by metals, Brønsted acids, Lewis acids or organocatalysts. The stereoselective reaction is feasible with satisfactory outcomes. This review summarizes the recent (2000–2019) meaningful papers in which the in-depth study and exploitation of this reactivity are reported.